Cell nuclei have lower refractive index and mass density than cytoplasm. Issue 10 (24th March 2016) - Schürmann, Mirjam; Scholze, Jana; Müller, Paul; Guck, Jochen; Chan, Chii J.
Abstract : Common perception regards the nucleus as a densely packed object with higher refractive index (RI) and mass density than the surrounding cytoplasm. Here, the volume of isolated nuclei is systematically varied by electrostatic and osmotic conditions as well as drug treatments that modify chromatin conformation. The refractive index and dry mass of isolated nuclei is derived from quantitative phase measurements using digital holographic microscopy (DHM). Surprisingly, the cell nucleus is found to have a lower RI and mass density than the cytoplasm in four different cell lines and throughout the cell cycle. This result has important implications for conceptualizing light tissue interactions as well as biological processes in cells. Abstract : Digital holographic microscopy is used to determine the refractive index (RI) and dry mass of isolated nuclei. Nuclear RI is found to be lower compared to whole cells in four cell lines. Changes to nuclear volume by electrostatic and osmotic conditions, and chromatin modifications, reveal a linear relationship between RI and mass density. These findings indicate a lower nuclear density compared to the cytoplasm also in the in situ situation.